The impact of digital economy development on carbon emissions -- based on the Yangtze River Delta urban agglomeration - Zha, Qifen; Huang, Chuan; Kumari, Sonia (Frontiers in Environmental Science, 2022)
The dual carbon target has been the focus of domestic attention since it was proposed. At the same time, the digital economy based on new technologies such as the Internet and big data has become an important engine to boost China's high-quality economic development. While the digital economy is promoting the development of the urban economy, can it also promote the low carbon development of cities in China? Based on panel data and multiple econometric models of 26 cities in the Yangtze River Delta urban agglomeration from 2006 to 2020, this paper empirically examines the impact of digital economy development on urban carbon emissions. The results show that the development of the digital economy can not only reduce the carbon emission intensity of this region but also effectively reduce the carbon emission intensity of surrounding areas. Therefore, it is necessary to further promote the construction of digital economy in the urban agglomeration, improve the inclusiveness and flexibility of the implementation of digital economy development strategy, and improve the construction of information infrastructure to give full play to the role of the digital economy in improving carbon emissions in urban agglomeration.